If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = (x + 4) + -25 Multiply f * x fx = (x + 4) + -25 Reorder the terms: fx = (4 + x) + -25 Remove parenthesis around (4 + x) fx = 4 + x + -25 Reorder the terms: fx = 4 + -25 + x Combine like terms: 4 + -25 = -21 fx = -21 + x Solving fx = -21 + x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -21x-1 + 1 Simplifying f = -21x-1 + 1 Reorder the terms: f = 1 + -21x-1
| 4x/9-7=1 | | .75(h+6)=15 | | 4x-2X+x+59= | | 12(z+2)-4(z-4)=3(z-1)+4(z-3) | | 10-d=-34+5d | | 5(n+8)=n+28 | | 8y+5/4=9y+1/4 | | -6x+3x=8-2x+4+16 | | x+y+x+y+2x+2z= | | 7x+2.0=-4x-5.3 | | 6(4x-9)-7=6(x-3)+65 | | 2x^2+24-60=0 | | 15x+20=20x-5 | | 6(4x-9)-7=6(x-3) | | x^2+6x+-55=0 | | .5(2x-2)=5x+4 | | f(x)=(x+6)-49 | | 48y^2-13y=0 | | -29=5(2a-1)+3 | | 4(x+2)=8(x-1)-12 | | 2n^2+11n-90=0 | | 7.512=4.2/x | | 9y^2-18=0 | | 4(2+3c)=96 | | -4(1-3b)=21+7b | | 11x-(3x-8)=64 | | 2(4z+4)-9=55 | | 4K+2=5.5 | | -6x=7+5x+5x | | 0x-6y=30 | | h(x)=(x+4)(x-6)(x-8) | | 7z+1/9=8z+2/9 |